To find the correlation between transverse cerebellar diameter measured by cranial ultrasound within 48 h of birth and gestational age as estimated by last menstrual period - Monit Kumar Goyal,; Harish Kumar Mourya,; Saroj Mourya,; Bharatendu Dave,; Pokar Chand,; Sundaramoorty T,; Vipin Kumar Kasana, (Asian Journal of Medical Sciences, 2024)
Background: Gestational age (GA) may be assessed at any time during pregnancy, and several modes of assessment exist, each requiring better diagnostic techniques that may result in more precise estimates of GA, which could lead to quicker medical management of a pregnant patient. The largest diameter across both hemispheres, measured from outer to outer margin, is the transverse cerebellar diameter (TCD). Aims and Objectives: We aimed to predict the correlation between TCD measured by cranial ultrasound within 48 h of birth and GA as estimated by the last menstrual period. Materials and Methods: The present study was conducted in the Department of Pediatrics, Dr. S. N. Medical College, Jodhpur, Rajasthan. Ethical clearance was obtained from the Institutional Ethical Committee. It was a cross-sectional observational study and the duration of the study was 6 months. We split the population into three groups based on GA: (a) <32 weeks of GA, (b) 32–36+6 days of GA, and (c) 37–42 weeks of GA. We enrolled 25 neonates from each group. Results: A very strong positive correlation between TCD and GA in infants was <32 weeks of gestation age, in infants 32–36 weeks+6 days of gestation age, and in infants 37–42 weeks of gestation age. Regression analysis shows a very strongly significant relationship. Hence, the TCD is a better predictor of GA in the third trimester. Our study reported that there is a close relationship between TCD and GA, with TCD increasing linearly from <32 weeks to 42 weeks. GA can be predicted to be 1.43 weeks by assessing TCD on neonatal cranial ultrasonography images. Conclusion: The TCD is a better predictor of GA in the third trimester. Our study reported that there is a close relationship between TCD and GA, with TCD increasing linearly from <32 weeks to 42 weeks.